Some socio-demographic features of mood disorders presented by patients attending a northern Nigerian tertiary health institution clinic - Oyeronke M. Aiyelero, Helen O. Kwanashie, Taiwo L. Sheikh, Isa M. Hussaini (Journal of Applied Pharmaceutical Science)
The aim of this study was to document some socio-demographic features of mood disorders in a Northern Nigerian tertiary health institution clinic. A retrospective evaluation of patients’ hospital records from1st January to 31st December 2006, using structured data forms which were analyzed with SPSS. All patients diagnosed of mood disorders (n=145) were included in the study sample. Mood disorders accounted for 26.0% of all patients who attended the Psychiatry clinic during the 1-year period, second only to schizophrenia (39.8%). Depression was the most prevalent sub-type of mood disorders (54.5%) followed by bipolar affective disorders (32.4%), hypomania (9.0%) and mania (4.1%). Majority of the patients with mood disorders were female (62.1%), below thirty years of age (57.2%), married (57.2%), had tertiary education (41.8%) and were unemployed (60.7%). Other features seen were: family history of psychiatry disorders in (29.0%) and substance abuse (13.1%), non-psychiatry co-morbid physical conditions (38.0%) were more prevalent than psychiatry co-morbid disorders (27.6%). These known features of mood disorders in this tertiary health institution clinic form valuable baseline data and would contribute to the pharmacological and other managements of the patients.
Keywords: Socio-demographic features, Mood disorders, Co-morbidity, Northern Nigeria, Health Institution.